General, regional and combination anesthesia in knee arthroplasty: A multicenter cohort-study of 15326 cases analyzing patient satisfaction and perioperative pain management. Issue 6 (28th June 2019) - Greimel, Felix; Maderbach, Günther; Baier, Clemens; Keshmiri, Armin; Schwarz, Timo; Zeman, Florian; Meissner, Winfried; Grifka, Joachim; Benditz, Achim
Aims and Objectives: In recent years, a steadily increasing number of total knee arthroplasty implants have been reported. After having ameliorated operation techniques and material, pain management and anesthetic methods have come into focus. Various anesthesia procedures for the surgical procedure itself as well as pain management programs have been developed. One of the main goals is to reduce postoperative pain and enable better and faster mobilization in the postoperative period. The present study aims to compare the use of general and regional anesthesia and their combination in terms of perioperative pain management and patient satisfaction. Materials and Methods: In the present cohort study, 15.326 patients were examined in 46 orthopedic departments after knee replacement surgery from 2009-2015. The parameters were analyzed on the first postoperative day as part of the project "QUIPS - Quality Improvement in Postoperative Pain Management", an initiative to compare the outcome parameters in participating hospitals. Primary outcome values were pain levels (activity, minimum and maximum pain, and pain management satisfaction) on a NRS scale. Pain medication necessity was analyzed using the WHO pain ladder classification. Parameters were compared between the types of anesthesia used: general, regional and combination anesthesia. Results: Pain scores and pain management satisfaction were significantly better in the groups of either spinal or peripheral anesthesia combined with general anesthesia (p0.001, respectively). Patients who received the combination of general and spinal anesthesia were associated with the lowest need for opioids (p0.001). Conclusion: The use of a combined general and spinal anesthesia as well as using a combination of general and peripheral anesthesia in knee arthroplasty was associated with a highly significant advantage to other anesthetic techniques regarding perioperative pain management in daily clinical practice, but maybe below clinical relevance. Furthermore they were associated with positive tendency considering side effects and subjective well-being parameters.